Epistemologi Pemikiran Jane Dammen McAuliffe Tentang Hubungan Al-Qur’an dan Tafsir - Mahfidhatul Khasanah (Nun: Jurnal Studi Alquran dan Tafsir di Nusantara, 2022)
The Qur'anic verse is indeed a text, which to understand it needs to be bridged by scholars who are qualified in the field of linguistic rules to produce an interpretation. Mufasirs and Muslims in general place interpretation as a reference for understanding the Qur'an, but for Jane Dammen McAuliffe, interpretation controls the meaning of the Qur'an. McAuliffe believes that the two cannot be equated and aligned as a way to understand the Qur'an. Thus, one cannot be generalized to represent the general view. The purpose of this article is to attempt to illustrate how McAuliffe views the relationship between the Qur'ān and tafsir as one of the Islamic thinkers. To further examine McAuliffe's thoughts, the method the author uses is library research with a content analysis approach. The results of this article are: First, McAuliffe explains that the interpretation of the Qur'an has been controlling the meaning of the Qur'an. Second, the Qur'an is morphologically unchanging, it lives semantically. Meanwhile, tafsir is considered as a particular hermeneutical configuration. From the results of this study, it can be concluded that the Qur'anic verse is indeed a text, which requires linguistic rules to understand. However, the text is also an integrated part of the context, stripping the context that should be attached to the text has the potential to cause gaps in meaning.